PENILAIAN TINGKAT KESEHATAN BANK DENGAN RASIO PROFITABILITAS PADA PT. BANK AGRIS TBK TAHUN 2013-2017 - Camelia Verahastuty; Ivana Nina Esterlin Barus (RJABM (Research Journal of Accounting and Business Management), 2019)
The purpose of this study was to determine the assessment of the Bank's soundness with Profitability Ratio at PT. Bank Agris in 2013-2017 in terms of ROA. The analytical tool used is Return on Assets (ROA) .The data needed is 5 years from 2013 to 2017 obtained from the Indonesia Stock Exchange. The results of this study: ROA in 2013 had a fairly healthy predicate then in 2014, 2015 and 2016 it fell to be unhealthy and 2017 decreased again to become unhealthy.The results of the hypothesis of this study Bank health rating with the RGEC method at PT. Bank Agris Tbk in 2013-2017 based on: 2013 ROA has a fairly healthy predicate then in 2014,2015 and 2016 it declined to be less healthy and 2017 declined again to become unhealthy, the hypothesis was rejected